2007
DOI: 10.1590/s0102-311x2007001600018
|View full text |Cite
|
Sign up to set email alerts
|

Decreased intelligence in children and exposure to fluoride and arsenic in drinking water

Abstract: Recent evidence suggests that fluoride (F) Febrero (F 9.4±0.9mg/L; As 194±1.3µg/L). The final study sample consisted of 132 children from 6 to 10 years old. After controlling for confounders, an inverse association was observed between F in urine and Performance, Verbal, respectively). Similar results were observed for F in drinking water (β values = -6.7, -11.2, -10.2, respectively) and As in drinking water (β values= -4.30, -6.40, -6.15, respectively). The p-values for all cases were < 0.001. A signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 13 publications
3
98
1
Order By: Relevance
“…Moreover, nitrite in the stomach due to acidic conditions is converted to N-nitroso compounds that have genotoxic potential in humans [24]. In addition, higher concentrations of fluoride in water samples in children result in impaired mental growth, plus skeletal and dental fluorosis [25]. The presence of total and fecal coliforms also indicates water contamination with animal and/or human wastes [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nitrite in the stomach due to acidic conditions is converted to N-nitroso compounds that have genotoxic potential in humans [24]. In addition, higher concentrations of fluoride in water samples in children result in impaired mental growth, plus skeletal and dental fluorosis [25]. The presence of total and fecal coliforms also indicates water contamination with animal and/or human wastes [26].…”
Section: Introductionmentioning
confidence: 99%
“…17 Saxena et al and Shivaprakash et al in their study have also demonstrated that intellectual capacity of children decreases with increase in the fluorosis grade. 6,19 Data from previous studies support to the hypothesis that interaction between fluoride, lead, and arsenic could worsen the children's intelligence grades, 20 and thus, indicate a need for further investigation. Guan et al demonstrated that the contents of phospholipids and ubiquinone are altered in the brain of rats affected by chronic fluorosis, and therefore changes in membrane lipids could be a cause of this disorder.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, As is a potent endocrine disruptor; thus, it may interact with estrogen and thyroid hormones, both of which are essential for brain development (Davey et al 2008). Several studies reported an association between exposure to arsenic and deleterious effects in IQ scores as well as in memory and performance domains in children aged 5-15 years (e.g., Rocha-Amador et al 2007;Hamadani et al 2011;Wasserman et al 2011). On the other hand, no significant effects were found between arsenic and behavioral disorders (Roy et al 2011;Yousef et al 2011;Khan et al 2012).…”
Section: The Effects Of Metal Co-exposurementioning
confidence: 99%